2010
DOI: 10.1007/s12325-010-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

The rate of metabolic syndrome in euthymic Canadian individuals with bipolar I/II disorder

Abstract: Asymptomatic Canadian individuals with bipolar disorder exhibit a high rate of concurrent metabolic syndrome. The results herein buttress recommendations for risk factor screening and modification, ongoing surveillance, as well as primary and secondary prevention strategies for metabolic abnormalities in individuals with bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
0
27
0
2
Order By: Relevance
“…Comorbid metabolic disturbances in patients with BD have been associated with a more complex illness presentation, less favourable response to treatment, and worse course of illness (283,287,288).…”
Section: Prevalence and Impactmentioning
confidence: 99%
“…Comorbid metabolic disturbances in patients with BD have been associated with a more complex illness presentation, less favourable response to treatment, and worse course of illness (283,287,288).…”
Section: Prevalence and Impactmentioning
confidence: 99%
“…Several studies have reported that metabolic syndrome tends to be associated with certain characteristics of bipolar disorder (Chang 2009;McIntyre 2010):…”
Section: Bipolar Disorder and Metabolic Syndromementioning
confidence: 99%
“…[455863] Some studies have found association between history of at least one suicide attempt and MetS,[43] others have reported no such association. [56] Similarly, comorbid substance use or smoking has been inconsistently associated with presence of MetS with some studies reporting higher prevalence of MetS in patients with comorbid substance use or smoking[9] and others have reported no such difference between those with MetS and those without MetS. [58] Studies have not found significant difference between patients with MetS and those without MetS with respect to presence of family history of lipid disorders or cardiovascular disease,[63] and rate of psychiatric comorbidity.…”
Section: Prevalence Of Components Of Metsmentioning
confidence: 99%
“…[58] Studies have not found significant difference between patients with MetS and those without MetS with respect to presence of family history of lipid disorders or cardiovascular disease,[63] and rate of psychiatric comorbidity. [56]…”
Section: Prevalence Of Components Of Metsmentioning
confidence: 99%